(Socialization Of Fermentation Feed For Meat Duck Farmers At The Village Of Tanjong Deyah) - Geubrina Maghfirah (Departemen of Animal Science, Agriculture Faculty, Syiah Kuala University, 2022)
ABSTRACT. The lack of enthusiasm of breeders in broiler duck farming is due to the large cost of feed with more quantity compared to chicken. Therefore, it is necessary to socialize the use of feed fermentation technology to utilize local feed raw materials that are around to reduce these costs. Community service activities held with the USK Charity House aim to introduce a way of fermenting duck feed to minimize weaknesses in traditional feeding. The participants were attended by lecturers from the livestock department of Syiah Kuala University, lecturers from the Serambi Mecca University, charity house volunteers, students, and duck farmers in Tanjong Deyah village who received benefits from the 1000 ducks program. The activity was carried out using lecture methods, question and answer, and the practice of making fermented feed. Materials are obtained from shops that sell poultry needs. The output of this activity is that duck farmers are able to ferment feed on local feed ingredients to improve feed quality and time efficiency in providing duck rations. The conclusion is that duck farmers are enthusiastic about participating in a series of events, because there are many benefits received in the socialization of fermented feed.